2023
DOI: 10.1097/md.0000000000034163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different lymph node dissection methods on the number of lymph nodes detected and prognosis in gallbladder cancer

Abstract: At present, the extent of lymph node dissection (LND) for radical gallbladder cancer (GBC) is still controversial, and there is no evidence that LND improves prognosis, however, the latest guidelines for GBC recommend that removal of more than 6 lymph nodes facilitates staging of regional lymph nodes. The aim of this study is to investigate the effect of different LND methods on the number of lymph nodes detected and assess the prognostic factors during radical resection of GBC. This study retrospectively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Another study in China of 133 patients found that fusion lymphadenectomy, which uses 3D-SPECT (photon emission CT) and CT or MRI data, may increase the number of both overall retrieved lymph nodes and positive lymph nodes. It improved both the diagnostic accuracy and survival[ 96 ]. A study of 227 GB carcinoma patients assessed the effect of three-dimensional visualization preoperative evaluation and enhanced recovery after surgery and found that precise surgery improved oncological outcomes.…”
Section: Managementmentioning
confidence: 99%
“…Another study in China of 133 patients found that fusion lymphadenectomy, which uses 3D-SPECT (photon emission CT) and CT or MRI data, may increase the number of both overall retrieved lymph nodes and positive lymph nodes. It improved both the diagnostic accuracy and survival[ 96 ]. A study of 227 GB carcinoma patients assessed the effect of three-dimensional visualization preoperative evaluation and enhanced recovery after surgery and found that precise surgery improved oncological outcomes.…”
Section: Managementmentioning
confidence: 99%